Community Participation in Land and Forest Fire Prevention and Mitigation in Indonesia: A Systematic Literature Review - Jaes, Lutfan; Rahman, Riki; Syamsuadi, Amir; Syahrier, Fajar Alan (Human Sustainability Procedia, 2025)
Community participation plays a central role in the prevention and mitigation of forest and land fires in Indonesia. However, the level of participation varies and is influenced by various factors based on local socio-economic and regional conditions. This study uses the Systematic Literature Review (SLR) method to examine how community participation influences the effectiveness of forest and land fire prevention and mitigation strategies, as well as identify challenges that hinder it and efforts to overcome them. Of the 328 articles found, 15 were analyzed in depth after going through a selection and quality assessment process. The results showed that community participation has a significant influence on the effectiveness of land and forest fire prevention and mitigation, with a positive correlation to a decrease in fire incidents in some areas with active participation. However, there were challenges that hindered participation, both internal and external factors. Internal factors include low motivation, limited human and financial resources, and minimal facilities and infrastructure. Meanwhile, external factors include lack of training, coaching, data integration, and lack of support from the government. To overcome these challenges, a comprehensive strategy is needed, including capacity building, community empowerment, and strong support and collaboration from the government and related agencies.